Pengaruh Stres Kerja dan Locus of Control terhadap Kepuasan Kerja dan Kinerja Pegawai Bagian Layanan PT Bank Negara Indonesia (Persero), Tbk. Cabang Malang - Savira, Halida; Noermijati; Djumahir (Jurnal Aplikasi Manajemen, 2014)
This study investigated the influece of job stress and locus of control to job satisfaction and job performance of employees in service division at PT. Bank Negara Indonesia (Persero), Tbk. in Malang using Partial Least Square. The population of the research covered the whole tellers and customer service officers in Bank BNI Malang, with 70 respondents as the research samples. The outputs of these findings indicate that the variable of job stress has direct and significant influence to the job satisfaction and job performance of tellers and customer service officers in Bank BNI Malang, and also has indirect and significant influence to the job performance through job satisfaction of tellers and customer service officers in Bank BNI Malang. Whereas, the variable of locus of control has a direct and significant influence to the job satisfaction and job performance of tellers and customer service officers in Bank BNI Malang, and also has indirect and significant influence to the job performance through job satisfaction of tellers and customer service officers in Bank BNI Malang. Last, variable job satisfaction has direct and significant influence to the job performance of tellers and customer service officers in Bank BNI Malang. These findings indicate that in order to improve job satisfaction and job performance of the employees can be carried out by keeping the level of job stress so that it will not increase to the negative level and also improving locus of control especially the internal locus of control.